Financial Resiliency of the Top Three Listed Companies in the Philippine Stock Exchange - Sasan, Caren C.; Polinar, Mark Anthony N.; Serafin, Ellen G.; Mahinay, Socorro T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The adverse effects of the ongoing pandemic caused big corporations to incur financial losses, which resulted in shrinkage of sales, increasing costs, and retrenchment. The entities' financial resilience was questioned, challenged, and business operations were paralyzed during the pandemic. Based on their market capitalization, this paper examined the top three listed companies in the Philippine Stock Exchange’s selected financial ratios if there were significant differences before and during the pandemic. Quantitative research using secondary data was used to quantify the mean and paired t-test based on the selected financial ratios. The results revealed that the current ratio, quick ratio, debt ratio, debt to equity, asset to equity, net profit margin, and return on assets had no significant effect on financial performance before and during the pandemic. Eventually, the return on equity showed a significant effect in the study. Therefore, presenting the findings, the study concluded that these companies were inefficient in generating profits and had a significantly high level of debt during the Covid-19 pandemic. Furthermore, a discussion about the benefits for the policymakers, potential and existing investors, and future researchers was also provided.